Effects of A 12-Week Rebound Therapy Exercise on Energy Consumption and Body Mass Index in Patients With Spinal Cord Injury - Morteza Sadeghi; Gholam Ali Ghasemi; Mohammad Taghi Karimi (Sport Sciences and Health Research)
Introduction: Energy Consumption (EC) and Body Mass Index (BMI) are the major complications associated with Spinal Cord Injury (SCI), which can be improved by exercise rehabilitation. Thus, the present study aimed to evaluate the efficiency of using rebound therapy (exercise on a trampoline) on EC and BMI in individuals with SCI.Materials and Methods: Sixteen individuals with SCI (ASIA classification: A=6, B=6, C=2, D=2) were selected and randomly divided into two groups of experimental (rebound exercise) and control. The experimental group performed the exercise program by a modified trampoline for 12 weeks (10-30 minutes; 3 sessions a week). EC was measured by the Physiological Cost Index (PCI) and BMI was calculated by standard formula before and after the exercise intervention. Finally, the obtained data were analyzed by Repeated-Measures Analysis of Variance (RM-ANOVA) in SPSS.Results: The results of RM-ANOVA revealed significant interaction in both criteria (P<0.01). In other words, the experimental group changes were substantial, compared to that of the control group.Conclusion: The collected results indicated that rebound therapy could, in effect, improve the SCI individuals’ EC and BMI. Furthermore, it was suggested that rebound exercise can be a useful sports rehabilitation method for patients with SCI.